Recovery of adults with autism spectrum disorder during intensive inpatient treatment: a qualitative study - Bloemert, Hendrikje; Sizoo, Bram B.; Verhoeven, Elisabeth W. M.; Beekman, Aartjan; van Meijel, Berno (Frontiers in Psychiatry, 2024)
Introduction Although some adults with autism spectrum disorder (ASD) require intensive and specialized ASD treatment, there is little research on how these adults experience the recovery process. Recovery is defined as the significant improvement in general functioning compared to the situation prior to treatment. Methods This qualitative study describes the recovery process from the perspective of adults on the autism spectrum during intensive inpatient treatment. Semi-structured interviews (n = 15) were carried out and analyzed according to the principles of grounded theory. Results Our results indicate that, given the specific characteristics of autism, therapeutic interventions and goal-oriented work cannot be carried out successfully, and the recovery process cannot begin, if no good working relationship has been established, and if care is not organized in ways that a person on the autism spectrum finds clear and predictable.